(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In the last 20 years, outer space has experienced tremendous growth, with the launch of Sputnik 1 by the Russians, the world has seen more countries either launch or show interest in exploring outer space and, there are currently 110 signatories to the outer space treaty. National security has led to main countries considering establishing their military presence in space, fear of some countries or individuals it using to attack each other has shifted how concerned people perceive space in its entirety, the questions as to who owns certain areas of space still loom across because states with presence in space claim pieces of land in space, this is exacerbating the increase in military activities in space, countries have started establishing space force.Currently Outer Space is governed through Space Treaty (1967) and other five protocols by the United Nations Office of Outer Space (UNOOSA). The said treaty was signed during the cold war between USSR and the USA, the space treaty came into law almost sixty years ago and it has become absolute, private businesses and modern technological advancements witnessed in recent passed are not addressed in the outer space treaty. its intended purpose was demilitarize Outer space because of fears that space could be for military purposes during the Cold war, The intention of outer space treaty was to ensure that outer space is used for peaceful purposes only, UNOOSA performs its mandate solely on information received from states with presence in outer space, it does not have a space station but depends on the goodwill of space agencies, and there are main questions with regards to the authenticity of information provided by the state parties because they are interested parties. The paper aims to provide solutions to the issues raised herein, this will be achieved by getting an insight into the administration of Outer space by COPUOS, the militarization of outer space and terrorism in space. Lastly, the research will explore the effectiveness of the Outer Space treaty of 1967 in the 21st century putting into consideration sovereignty and concluding by providing solutions to the same.